Building deductive object-oriented database systems in the ODMG era - Falcone Sampaio, Pedro R (Information and software technology, 2001)
Deductive object-oriented database systems (DOODs) have been a subject of intensive research for the last 13 years, with results embodied in several research prototypes and one commercial system produced so far [1]. However, despite the considerable number of systems available, there has been surprisingly little work on organising and analysing the several system architectures and query processing strategies that have been employed in the construction of DOODs. Furthermore, with the consolidation of the ODMG specification as a standard for object databases, it is important to assess which architectural approach is better suited for building DOODs considering the ODMG framework. This paper categorises several representative DOOD systems based on their architecture and query processing approach, and provides an analysis of the issues involved in building DOOD systems compliant with the ODMG standard.